THROUGH TEACHING YOUTH FOREIGN LANGUAGES PREPARATION QUALIFIED PERSONNEL FOR THE LABOR MARKET: PROBLEMS AND SOLUTIONS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
In this article, the processes of training qualified personnel for the labor market by teaching foreign languages to young people are classified. At the same time, data on ensuring their employment by training them in professions that are in high demand in the domestic and foreign labor markets and teaching them foreign languages was analyzed. Proposals and recommendations have been developed to ensure employment of young people in the domestic and foreign labor market by teaching foreign languages and vocational training in educational institutions.
Keywords: labor market, domestic and foreign labor market, vocational training, learning foreign languages, high education, technical schools, vocational skills centers, qualified personnel, graduates of educational institutions, quality of education, educational processes, video content in foreign languages, online classes, international certificates determining the level of knowledge of foreign languages.